Management of odjects of communal ownership right: an innovative approach - Serdiukova , Olena (Theory and Practice of Public Administration, 2019)
Problem statement. The Law of Ukraine “On Amendment to Certain Legislative Acts of Ukraine on Management of State and Communal Ownership Objects”, adopted on June 2, 2016, completely changed the concept of the communal enterprise management. For unitary communal enterprises, creation of such a governing body as a supervisory board was regulated by the law for the first time, which in its turn influenced the activities of local self-government bodies, leaving them some time to hesitate about the need to create or not to create them, identifying advantages and disadvantages of the newly elected governing body.Analysis of recent research and publications. In research literature, a considerable number of works of Ukrainian and foreign scientists are devoted to the issue of increasing the management efficiency of communal enterprises based on usage of various management tools.As a short period of time has passed since the entry of the above-mentioned law (June 2016) into force, and today there are only individual cases of formation of supervisory boards at communal enterprises in different regions of Ukraine, the problems of their formation and functioning as an innovative management tool, as well as solutions of these problems have not yet been studied in detail in research works of Ukrainian scientists. Therefore, this issue has a practical research interest.Purpose statement. The purpose of this article is to determine the problems of establishment and functioning of supervisory boards as communal enterprise management bodies in Ukraine and ways of their solution.Presentation of basic material. Subjects of communal services created by local self-government bodies have been requiring implementation of innovative management methods and technologies that will allow them to become more competitive in the market, to achieve stability and to really become subjects of sustainable development of territories.The priority of the public role in solving local issues, in particular control over the activities of government bodies, is determined by the Strategy for Sustainable Development “Ukraine 2020”. Now, through supervisory boards established by local self-government bodies the public gets the right to control their activities, to directly implement their management policy, to create a strategy for their sustainable development.The insignificant experience of establishment and functioning of supervisory boards at communal enterprises allowed the existing problems to be divided into three groups: regulatory, organizational and personnel, financial and economic.In our point of view, the criteria for establishment of supervisory boards at communal enterprises have their own peculiarities, which can include a settlement type and size, the number of its inhabitants, the state of local economic development, the structure of the settlement economy, etc. All these factors influence definition of criteria according to which supervisory boards should be formed at community enterprises, without additional problems for financial state of enterprises.In case of adoption of the decision on the need for establishment of supervisory boards at communal enterprises by local self-government bodies, the criteria for their formation should be:1) The net income level of the unitary communal enterprise or economic entity according to the data of the latest annual financial statement.2) The amount of the authorized capital of the newly created unitary communal enterprise, economic entity as on the date of its formation.3) The number of employees working at the enterprise.At the same time, the maximum size of these criteria is determined by local self-government bodies and may be different in different settlements.An effective instrument for controlling the activities of the communal enterprise and its head is also a balance commission established by the local self-government body. The commission listens to the report of the enterprise head on the results of the activity and fulfilment of the contract terms at least once a year.Conclusions and prospects of further research. Thus, the practice of applying the state-defined innovative approach to formation of a management system of legal persons by public law through creating supervisory boards at them under modern conditions has certain disadvantages and should be improved by amending the existing regulations and creating the new ones of a local nature. The state should clearly define the criteria for formation of supervisory boards, their functions and powers, both at state and communal enterprises, the procedure of election and dismissal of its members.Further research in this direction will be related to development of a functioning mechanism of supervisory boards in terms of avoiding the risk of involvement of engaged and unscrupulous public representatives in supervisory boards of communal enterprises, taking into account the results of studying foreign experience concerning these issues.